Studi literatur: Pengaruh model discovery learning terhadap perkembangan keterampilan proses sains pada berbagai jenjang pendidikan di Indonesia - Jeanis Janah Sofiastri; Siti Shofa Assyifaul Qulbi Barid; Sri Wahyuni; Sri Rejeki Dwi Astuti (Papanda Publisher, 2026)
Science process skills represent fundamental abilities that must be strengthened in 21st-century education, as they support students in developing scientific ways of thinking, solving problems, and constructing conceptual understanding. Data from the 2022 Programme for International Student Assessment (PISA) show that Indonesian students achieved a science score of 383, a decline from 396 in 2018, which reflects the limited development of essential scientific skills. This study analyzes the role of the Discovery Learning model in enhancing students’ science process skills at elementary, junior high, and senior high school levels in Indonesia. The research employed a Systematic Literature Review method following PRISMA guidelines. An initial search of Google Scholar using the keywords Discovery Learning, Science Process Skills, and Science identified 4,820 articles. After applying inclusion and exclusion criteria, 28 relevant studies published between 2021 and 2025 were analyzed, consisting of 4 elementary, 12 junior high, and 12 senior high school studies. The findings consistently show that Discovery Learning positively influences science process skills through observing, experimenting, and drawing conclusions based on empirical evidence. Across educational levels, this model supports scientific reasoning, critical thinking, and scientific attitudes. This review contributes to science education by synthesizing evidence on the implementation of Discovery Learning across educational levels, providing a structured reference for educators and researchers to strengthen science process skills instruction. In addition, the findings highlight opportunities for future studies to integrate Discovery Learning with digital technologies and interdisciplinary approaches to further enhance students’ scientific competencies